Using a variant of coverslip hypoxia to visualize tumor cell alterations at increasing distances from an oxygen source. Issue 10 (25th March 2019) - Arocena, Miguel; Landeira, Mercedes; Di Paolo, Andrés; Silva, Alejandro; Sotelo‐Silveira, José; Fernández, Ariel; Alonso, Julia
Abstract: Early stages in tumor development involve growth in confined spaces, where oxygen diffusion is limited and metabolic waste products accumulate. This hostile microenvironment imposes strong selective pressures on tumor cells, leading eventually to the survival and expansion of aggressive subclones that condition further tumor evolution. To model features of this microenvironment in vitro, a diffusional barrier can be introduced in the form of a coverslip placed on top of cells, a method termed coverslip hypoxia. Using a variant of this method, with larger volume between coverslip and cells and with oxygen diffusion occurring only through a small hole in the center of the coverslip, we have visualized alterations in LNCaP tumor cells as a function of their distance to the oxygen source at the center. We observed remarkable morphological changes in LNCaP cells as the distance from the center increases, with cells becoming highly spread, displaying dynamic membrane protrusions and occasionally adopting a migratory phenotype. Concomitantly, cells farther from the center displayed marked increases in the hypoxia marker hypoxyprobe, whereas extracellular pH decreased in the same direction. Cells with altered morphology displayed prominent increases in fibrillar actin, as well as swollen mitochondria with distorted cristae and accumulation of neutral lipid‐containing intracellular vesicles. These results show that an in vitro microenvironment that models diffusional barriers encountered by tumors in situ can have profound effects on tumor cells. The coverslip hypoxia variant we describe can be used to characterize in vitro the response of tumor cells to environmental conditions that play crucial roles in early tumor development.